Overcoming Emotional Disorders in Hypertension Patients Through Al Fashdu Therapy - Salsaabila, Fiiki Minahul Ilmiah; Varaee, Payam (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2025)
Al Fashdu therapy is an Islamic psychotherapy that uses the Al Fashdu technique as one of the methods in its therapy process. Al Fashdu therapy is considered to be able to cure various diseases, one of which is the symptoms of hypertension. The symptoms experienced by hypertension patients are divided into two aspects, namely physical and psychological. The psychological symptoms of hypertension are emotional disorders. Emotional disorders are a condition where a person's emotional response is too weak or too strong in certain situations. The purpose of this study was to determine emotional disorders and Al Fashdu therapy to overcome emotional disorders in hypertension patients at the Kajen Pekalongan Therapy House. This study uses a type of field research with a descriptive qualitative method. The data collection techniques used are observation, interviews, and documentation. The results of this study indicate that hypertension patients at the Kajen Pekalongan Therapy House experience moderate emotional disorders, which are characterized by excessive angry responses when facing everyday problems. This arises because the physical symptoms of hypertension then trigger psychological symptoms. Al Fashdu therapy can overcome these physical symptoms, so that the psychological symptoms of hypertension, namely emotional disorders, are reduced, which are shown by being calm in facing problems. This study provides a positive contribution in overcoming emotional disorders in hypertensive patients, including increasing the ability to control emotional disorders through Al Fashdu therapy.